Chomsky and Skinner and the controversy over the generativity of language. (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
Verbal Behavior is considered to be B. F. Skinner’s most important work. On account of its importance, this book has been widely discussed and critiqued. One criticism came in the Review by N. Chomsky, which had, as one of its fundamental arguments, the idea that Verbal Behavior would not address the generative nature of human language. Set against this context, the objective here was to present the Review, by systematizing the arguments and signaling how Chomsky considered the behaviorist view would be unable to account for the generativity of language, and then to demonstrate how Skinner's Verbal Behavior has arguments that can address this generative character. As a backdrop to the discussion, a brief historical analysis of the two works was performed in order to better understand the context of the publications.
Keywords: Verbal generativity; Verbal behavior; Chomsky; Skinner